2016
DOI: 10.1590/0037-8682-0175-2015
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal efficiency of the mushroom Amanitamuscaria (Agaricales, Amanitaceae) against the mosquito Culexquinquefasciatus (Diptera, Culicidae)

Abstract: Introduction:We report the larvicidal activity of two formulations from Amanita muscaria against Culex quinquefasciatus, as well as the viability of the aqueous extract after storage. Methods: The larvicidal activity of aqueous extract and powder from A. muscaria, and the viability of the aqueous extract after storage, were evaluated. Results: The aqueous extract caused larval deaths, which varied from 16.4% to 88.4%. The effi ciency of the powder varied from 29.2% to 82.8%. Storage did not interfere with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…We observed that the larvicidal effect was dosedependent, as reported by Cárcamo et al (2016) for Culex quinquefasciatus (Diptera, Culicidae) larvae subjected to the same fungal species. However, the efficiency that we observed was lower than observed by these authors.…”
Section: Larvicidal Efficiency Of Fly Agaric Against the House Flysupporting
confidence: 84%
See 1 more Smart Citation
“…We observed that the larvicidal effect was dosedependent, as reported by Cárcamo et al (2016) for Culex quinquefasciatus (Diptera, Culicidae) larvae subjected to the same fungal species. However, the efficiency that we observed was lower than observed by these authors.…”
Section: Larvicidal Efficiency Of Fly Agaric Against the House Flysupporting
confidence: 84%
“…Nevertheless, it can only be produced in colder seasons when fresh basidiomes of A. muscaria grow in Rio Grande do Sul, Brazil (BERNARDI, E.: personal communication, 2015). On the other hand, the DPB extract can be stored up to six months without losing efficiency (CÁRCAMO et al, 2016).…”
Section: Larvicidal Efficiency Of Fly Agaric Against the House Flymentioning
confidence: 99%
“…These bioactive compounds may act as insecticides, antifeedants, moulting hormones, oviposition deterrents, repellents, juvenile hormone mimics, growth inhibitors, antimoulting hormones as well as attractants. Important also will be the identification of any toxic element or injurious fractions whose use should be actively discouraged [5]. Plant based pesticides are less toxic, delay the development of resistance because of its new structure and easily biodegradable [6][7][8].…”
Section: Introductionmentioning
confidence: 99%